Toxicity assessment of mastic and pomegranate tinctures using the Artemia salina bioassay (Research, Society and Development, 2021)
This work aimed to evaluate the toxicity of the mastic (Myracrodruon urundeuva) and pomegranate (Punica granatum) tinctures through the bioassay with Artemia salina. Different dye concentrations (25, 50, 75, 150, 250, 500, 750 and 1000 μg/mL) were added to the nauplii and the average lethal concentration (CL50) was evaluated using Probit analysis using the StatPlus® software (AnalystSoft, USA), obtaining the upper and lower confidence intervals, after a 24-hour exposure period. The extracts were considered active when the values were < 1000ug/mL. Survival curves and LogRank tests were performed for all extracts at a concentration of 250 μg / mL against negative control (Saline) and positive control (Chlorhexidine), using the GraphPad® Prism software (GraphPad Software, USA). For the mastic, the LC50 was 607.87 ± 38.73, for the pomegranate, 464.98 ± 28.72, both tinctures being considered active. When compared to saline, there was a significant difference in survival curves (p = 0.0206), the same occurred for comparisons with chlorhexidine (p < 0.0001). It can be concluded that mastic and pomegranate tinctures were toxic against Artemia salina in the different concentrations tested.